2019
DOI: 10.1128/jvi.01499-19
|View full text |Cite
|
Sign up to set email alerts
|

Host CARD11 Inhibits Newcastle Disease Virus Replication by Suppressing Viral Polymerase Activity in Neurons

Abstract: Host factors play multiple essential roles in the replication and pathogenesis of mammalian neurotropic viruses. However, the cellular proteins of the central nervous system (CNS) involved in avian neurotropic virus infection have not been completely elucidated. Here, we employed a gene microarray to identify caspase recruitment domain-containing protein 11 (CARD11), a lymphoma-associated scaffold protein presenting brain-specific upregulated expression in a virulent neurotropic Newcastle disease virus (NDV)-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 51 publications
2
23
0
Order By: Relevance
“…The expression of CARD11 was not significantly induced by velogenic and lentogenic strains in the infected CEFs and DF-1 cells. However, CARD11 was able to inhibit viral replication and suppress viral polymerase activity in fibroblasts, which was consistent with the results of our previous study ( Wang et al, 2019 ). Importantly, we found that CARD11 inhibited the fusogenic activity of NDV by activating the CBM signalosome to suppress furin expression, resulting in reduced cleavage efficiency of the F protein.…”
Section: Introductionsupporting
confidence: 93%
See 3 more Smart Citations
“…The expression of CARD11 was not significantly induced by velogenic and lentogenic strains in the infected CEFs and DF-1 cells. However, CARD11 was able to inhibit viral replication and suppress viral polymerase activity in fibroblasts, which was consistent with the results of our previous study ( Wang et al, 2019 ). Importantly, we found that CARD11 inhibited the fusogenic activity of NDV by activating the CBM signalosome to suppress furin expression, resulting in reduced cleavage efficiency of the F protein.…”
Section: Introductionsupporting
confidence: 93%
“…The CPE was visualized under an Olympus IX73 inverted research microscope (Japan). The viral titers of F48E9-infected cells were determined by a 50% tissue culture infective dose (TCID 50 /mL) assay, while those of LaSota-infected DF-1 cells were determined by an immunofluorescence assay (IFA) in DF-1 cells ( Wang et al, 2019 ). The titer of TCID 50 /mL was calculated according to the method established by Reed and Muench ( Guo et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The animals were subcutaneously injected with a mixture of the protein and incomplete Freund’s adjuvant (Sigma) at 14 and 28 days. After the guinea pigs were anesthetized with ketamine and xylazine, their antisera were collected and stored at − 80 °C [ 24 ].…”
Section: Methodsmentioning
confidence: 99%